Stavudine delivery in an extended release formulation: Will it provide the right in vivo pharmacokinetics — Some key observations (Asian Journal of Pharmaceutics (AJP), 2014)
Saravanakumar et al, (2010) have performed anextensive study to enable the delivery of stavudinein a once daily extended release formulation.[1] Thein vitro evaluation has been performed with multipleformulation options to enable the selection of theright formulation system that renders once-a-daydelivery of stavudine, ensuring that zero order releaseis maintained during the entire duration. As evidencedby the generated data, the recommended formulation(F9), appears to release approximately 4% of the drugload every hour leading to a complete release of thestavudine drug load by 24 hours.